Bell's palsy in pregnancy and the puerperium: a report of five cases (2010)
The incidence of idiopathic facial nerve palsy is higher during pregnancy and the puerperium than in non-pregnant women of childbearing age. An important association also exists between Bell’s palsy and hypertensive disorders of pregnancy. We describe three patients with idiopathic facial nerve palsy in pregnancy and two in the puerperium. Two of these were associated with hypertensive disorder of pregnancy. This case report illustrates the fact that Bell’s palsy is common in pregnancy and in the puerperium and often associated with hypertensive disorders of pregnancy. Association also exists between Bell’s palsy and hypertensive disorders of pregnancy [1].The clinical manifestation is the same in pregnancy as in the general population, although, it tends to run a more severe course in the former [5]. Rarely, patients have recurrent Bell’s palsy in successive pregnancies [5]. Short course of steroids early in the course of the disease has been used with some evidence of benefit [7]. We present a crop of five cases of Bell’s palsy who we saw in quick succession within a few months at the Neurology Unit of the Department of Medicine, University College Hospital, Ibadan.